2019
DOI: 10.1021/acs.energyfuels.9b00865
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ring Deposits Inside a Quicklime Producing Long Rotary Kiln

Abstract: Ring deposits are common problems in rotary kiln operations. The ring is constantly subjected to thermal and mechanical wear counteracting the growth of the ring. If the ring hardens or if the growth of the ring is too rapid, the kiln needs to be shut down and the ring removed, reducing the operational time and profitability of the process. In the present study, ring deposits from a limestone fed long rotary kiln producing quicklime was sampled and characterized in detail by SEM-EDS, dynamic rate TG, and XRD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…To reduce the residence time and increase production capacity, the quicklime temperature in a lime kiln reaches 1100-1450 • C [15,16], far exceeding the calcination temperature of 800-900 • C. After calcination, the quicklime continues to exhibit phase transformations as the temperature in the lime kiln increases, and the final phase composition will depend on the maximum temperature reached. Eventually, the final product quality is also influenced by cooling, post-processing such as crushing and sieving, storage, and transport to the end user.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the residence time and increase production capacity, the quicklime temperature in a lime kiln reaches 1100-1450 • C [15,16], far exceeding the calcination temperature of 800-900 • C. After calcination, the quicklime continues to exhibit phase transformations as the temperature in the lime kiln increases, and the final phase composition will depend on the maximum temperature reached. Eventually, the final product quality is also influenced by cooling, post-processing such as crushing and sieving, storage, and transport to the end user.…”
Section: Introductionmentioning
confidence: 99%
“…Deposit formation in a rotary kiln is frequently observed in iron ore pellet production by the grate-kiln process, disturbing normal production and decreasing productivity . The deposit of fluxed iron ore pellets is more severe than acidic iron ore pellet production. , …”
Section: Introductionmentioning
confidence: 99%
“…10 The deposit of fluxed iron ore pellets is more severe than acidic iron ore pellet production. 11,12 Many researchers 13−19 have focused on the deposition mechanism in rotary kilns for acidic iron ore pellet productions. In the rotary kilns fueled by pulverized coal, preheated iron ore pellet powder and coal ash are the material basis for deposit formation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed mature deposits formed in industrial rotary kilns, calciners, and preheaters. An overview of the crystalline phases found in mature deposits formed during cement production and their typical locations are shown in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the amount of volatile constituents in any local part of the kiln charge was recommended as a precautionary measure to prevent the formation of the coating. Eriksson et al 32 sampled ring deposits from a rotary kiln when the plant was shut down and identified three hardening mechanisms of the deposits, referring to the increased densification of ring deposits, the formation of calcite and spurrite, and the intrusion of molten fuel ash into the refractory, resulting in a strong attachment of the deposit to the refractory. Belgacem et al 24 investigated the form and amount of the compounds in different deposit samples from the kiln inlet and proposed that the fluctuating operating temperature and the low calcination degree were the main reasons for the ring formation and growth.…”
Section: Introductionmentioning
confidence: 99%